Effects of helicobacter pylori on tumor microenvironment and immunotherapy responses - Deng, Ruiyi; Zheng, Huiling; Cai, Hongzhen; Li, Man; Shi, Yanyan; Ding, Shigang (Frontiers in Immunology, 2022)
Helicobacter pylori is closely associated with gastric cancer. During persistent infection, Helicobacter pylori can form a microenvironment in gastric mucosa which facilitates the survival and colony formation of Helicobacter pylori. Tumor stromal cells are involved in this process, including tumor-associated macrophages, mesenchymal stem cells, cancer-associated fibroblasts, and myeloid-derived suppressor cells. The immune checkpoints are also regulated by Helicobacter pylori infection. Helicobacter pylori virulence factors can also act as immunogens or adjuvants to elicit or enhance immune responses, indicating their potential applications in vaccine development and tumor immunotherapy. This review highlights the effects of Helicobacter pylori on the immune microenvironment and its potential roles in tumor immunotherapy responses.